A structural model of the antecedents and consequences of internal crisis communication - Adamu, Adamu Abbas (2018)
Internal crisis communication has identified as a new area of study in crisis management research. In fact, extant literature has indicated a lack of theoretical development on this dimension of crisis communication. Even more, literature search shows that the measurement of internal crisis communication is lacking. Consequently, the objective of this study is to develop a valid measures for internal crisis communication. Moreover, the study examine the relationships between social media usage, leadership, crisis responsibility and error management culture on internal crisis communication as well as its impact on affective commitment and perceived organizational support in Nigerian context. In addition, Situational Crisis Communication Theory, Sensemaking Theory and Transformational Leadership Theory were used as theoretical foundation. The study employed a mixed methods approach with a dominant quantitative component. The first part of the study involves a semi-structured interviews (with 10 respondents) and content validity (with 18 expert opinions). Secondly, a pilot survey (with 60 respondents) to collect data for the development of measurement scales. Thereafter, the main survey (with 325 respondents) was conducted in order to test the research hypotheses and the proposed conceptual model. In particular, structural equation modelling was applied. The study developed an 11 items measures for the focal construct. Overall, the results depicted an accepted fit for the data, with satisfactory convergent, discriminant and nomological validity and reliability. From the statistical findings, together with support from the literature and the semi-structured interviews during the exploratory stage, this study finds significant relationships between leadership, error management culture and internal crisis communication. However, social media usage has a significant but negative relationship while crisis responsibility does not have a significant relations hip with internal crisis communication. Similarly, as expected, it was found that internal crisis communication is positively and significantly related to affective commitment and perceived organizational support. As managerial and policy recommendations, crisis managers should emphasize more on the need for organizational leaders to include employees as primary stakeholders during crisis situation. In addition, the policy makers should strive to gain a positive image through showing support and commitment to their employees’ welfare and wellbeing during crisis. Finally, directions for future research were discussed.